2017
DOI: 10.3144/expresspolymlett.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

How high pressure CO2 impacts PLA film properties

Abstract: Abstract. This work investigated the sorption and the diffusion properties of CO 2 under high pressure and the further modifications induced in Poly(lactic acid) (PLA) thin layers. Poly(ethylene terephtalate) (PET) was also considered for comparative purposes. Firstly, from thermodynamic equilibrium, the CO 2 sorption isotherm (two sorption-desorption cycles, up to 25 bar, at 25°C) gave strong evidence of a physisorption mechanism and of a hysteresis phenomenon. Infrared spectroscopy analysis confirmed that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…PLA has high strength (* 60 to 65 MPa) and high modulus (* 2.5 to 3.0 GPa), which makes it suitable for applications like bottles, office utensils, cups and trays. By modifications like plasticizing or flame retarding, it can even be used as a film for food packaging [24], or in electronic and automotive applications [25]. Nevertheless, PLA also has two main drawbacks that highly limit its widespread application: its low heat deflection temperature (HDT) (* 50 to 55°C) and low impact strength (* 3 kJ m -2 notched Charpy impact strength) [6].…”
Section: Introductionmentioning
confidence: 99%
“…PLA has high strength (* 60 to 65 MPa) and high modulus (* 2.5 to 3.0 GPa), which makes it suitable for applications like bottles, office utensils, cups and trays. By modifications like plasticizing or flame retarding, it can even be used as a film for food packaging [24], or in electronic and automotive applications [25]. Nevertheless, PLA also has two main drawbacks that highly limit its widespread application: its low heat deflection temperature (HDT) (* 50 to 55°C) and low impact strength (* 3 kJ m -2 notched Charpy impact strength) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Next, Figure 6b shows FTIR measurements of PAN nanofiber mats on 3D printed PLA. Figure 6a gives an overview of typical peaks of PLA [51,52,53,54] (grey lines) and PAN [55] (red lines), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The sorbed quantity was rather high than the values reported in the literature for PLA films under similar pressure and temperature conditions. [45,47,52] In the same conditions (15 bar and room temperature (RT)), Rocca-Smith et al [49] reported, in fact, an adsorbed quantity of CO 2 equal to 4%, which is similar to the adsorption capacity of cPLA and pPLA, while it is half of that recorded for the fPLA sample. The highest absorption of fPLA can be attributed to the morphology and crystalline structure of the sample.…”
Section: Co 2 Adsorption/desorption Measurementsmentioning
confidence: 89%
“…Up to now, the related literature is mainly focused on the effects of supercritical CO 2 on the PLA properties and so there is not enough available information related to the effects of CO 2 at conditions lower than its supercritical point. [49] Properties of PLA depend on its component isomers, processing temperature, annealing time, and molecular weight (Mw). [50] In particular, the PLA lactides are formed by the condensation of two molecules of lactic acid, so three types of lactides can be obtained: dd-lactide, ld-lactide Poly-Dlactide acid (PDLA) and ll-lactide poly l-lactic acid (PLLA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation